SUSTAINABLE AGRICULTURAL PRACTICES OF THE CITOREK INDIGENOUS COMMUNITIES AND ITS IMPLICATIONS FOR THE DEVELOPMENT OF THE PROJECT TO STRENGTHEN THE PROFILE OF PANCASILA STUDENTS IN PRIMARY SCHOOLS - Maslihah Zahrah Agustina; Futihat Amini; Ila Rosmilawati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to identify sustainable agricultural practices and the character values of the Citorek indigenous people in it, as well as its implications in learning the project to strengthen the profile of Pancasila students in elementary schools. The method used is a qualitative approach with the ethnographic method, which involves interviews, observations, and documentation. The results of the study show that character values such as mutual cooperation, responsibility, and respect for ancestors are very strong in the sustainable agricultural practices of the Citorek community. The integration of these values in education not only enriches the learning experience of students, but also forms a character rooted in the local culture, supporting a just and sustainable life